The motif of yūrei in Japanese survival horrors – the analysis of selected case studies - Staszenko, Dominika (Replay. The Polish Journal of Game Studies, 2014)
This paper examines the phenomenon of survival horror games. It focuses on yūrei, a Japanese mythological supernatural being. Yūrei returns to the world of the living to take revenge on the people who harmed them in the past. The paper also concentrates on the remediation of yūrei iconography from literature and Japanese ghost movies into games. It analyses the characteristics of the survival horror genre, dividing them into the ludic and semantic systems. It also describes the relationships between traditional Japanese legends and modern texts, and presents an important issue of the main character (usually schematic and doomed to failure). Observations are based mainly on two games: Calling for Nintendo Wii and Kuon for PlayStation 2.